2013
DOI: 10.5114/pjp.2013.34605
|View full text |Cite
|
Sign up to set email alerts
|

Primary leiomyosarcoma of the mesentery in two sisters: clinical and molecular characteristics

Abstract: Mesenteric leiomyosarcoma (LMS) is a very rare malignancy whose familiar occurrence has not yet been reported. We present two sisters who developed intestinal LMS. Pathological analysis of the tumor samples, including evaluation of smooth muscle actin+, desmin+, Myf4-, DOG-1-, S100-, CD34-and CD117-confirmed LMS diagnosis. Molecular analysis of the lesions, both primary tumors and a liver metastasis, revealed several genomic imbalances, with recurrent chromosomal aberration: interstitial gain at chromosome 17p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Only 2 patients, including the one reported in this study, developed single liver metastasis (5). Three cases, including the patient reported in our study, underwent surgery for liver metastasis (6), and 3 cases received chemotherapy for the metastatic lesions (5,7). There is no mention of surgical intervention or chemotherapy treatment for the secondary liver lesions in the remaining 3 cases.…”
Section: Discussionmentioning
confidence: 90%
“…Only 2 patients, including the one reported in this study, developed single liver metastasis (5). Three cases, including the patient reported in our study, underwent surgery for liver metastasis (6), and 3 cases received chemotherapy for the metastatic lesions (5,7). There is no mention of surgical intervention or chemotherapy treatment for the secondary liver lesions in the remaining 3 cases.…”
Section: Discussionmentioning
confidence: 90%
“…Koczkowska M (2013) [6] 46-year-old female; detected during surgery for uterine myoma Surgical resection Recurrences at 6 and 9 months; died after 4 years and 10 months of initial diagnosis Sidhic AK (2015) [11] 33-year-old male; abdominal pain Surgical resection Not mentioned Present study (2015) 62-year-old female; heaviness and fullness of the abdomen Surgical resection, no radiotherapy or chemotherapy…”
Section: Discussionmentioning
confidence: 95%
“…Cappellani A et al presented a case of mesocolic and duodenal leiomyosarcoma with muscular metastases [5]. Interestingly, Koczkowska M et al reported two sisters who presented with primary mesenteric leiomyosarcomas, raising questions about familial occurrence of the tumor [6].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The surgery is a mainstay of treatment for this type of tumour as it is notoriously resistant to radiotherapy and chemotherapy 15. Earlier detection by CT together with complete oncological resection may improve long-term prognosis in patients with primary leiomyosarcoma of mesenteric origin 16.…”
Section: Discussionmentioning
confidence: 99%